The Use of Search Engines in the Marketing of Accommodation Establishments: Adopt or Reject the Use of Google AdWords? - Cant, Michael Colin; Rooyen, Nadine van (International Review of Management and Marketing, 2017)
The digital marketing world has become an everyday part of life for almost all businesses, and many incorporate social media and other electronic media into their strategies. It is also a known fact that many companies do not optimise these electronic media to its fullest due to a variety of reasons. The aim of this research study was to firstly investigate the awareness of Google AdWords and secondly to establish the use of Google AdWords among star-graded overnight accommodation establishments. The study was conducted among star-graded overnight accommodation establishments in the Western Cape, a strongly competitive market resulting in an increased need for targeted, affordable marketing tools. An empirical study was executed which enabled the quantitative capturing of the use of Google AdWords among these establishments thereby addressing of the research objectives in full. The result of this research study indicates that a general perception exists regarding Google AdWords as being difficult to use, thus deterring the adoption thereof among many establishments. This however, is countered by establishments that do make use of Google AdWords as an e-marketing tool, in that it is perceived as a successful e-marketing tool among these establishments. Keywords: Google AdWords; search engine optimisation; star-graded overnight accommodation establishments JEL Classification: M30 G M T <input id="SL_locer" title="Lock-in language" type="checkbox" /> <select id="SL_lng_from"><option value="auto">Detect language</option><option value="af">Afrikaans</option><option value="sq">Albanian</option><option value="ar">Arabic</option><option value="hy">Armenian</option><option value="az">Azerbaijani</option><option value="eu">Basque</option><option value="be">Belarusian</option><option value="bn">Bengali</option><option value="bs">Bosnian</option><option value="bg">Bulgarian</option><option value="ca">Catalan</option><option value="ceb">Cebuano</option><option value="ny">Chichewa</option><option value="zh-CN">Chinese (Simplified)</option><option value="zh-TW">Chinese (Traditional)</option><option value="hr">Croatian</option><option value="cs">Czech</option><option value="da">Danish</option><option value="nl">Dutch</option><option value="en">English</option><option value="eo">Esperanto</option><option value="et">Estonian</option><option value="tl">Filipino</option><option value="fi">Finnish</option><option value="fr">French</option><option value="gl">Galician</option><option value="ka">Georgian</option><option value="de">German</option><option value="el">Greek</option><option value="gu">Gujarati</option><option value="ht">Haitian Creole</option><option value="ha">Hausa</option><option value="iw">Hebrew</option><option value="hi">Hindi</option><option value="hmn">Hmong</option><option value="hu">Hungarian</option><option value="is">Icelandic</option><option value="ig">Igbo</option><option value="id">Indonesian</option><option value="ga">Irish</option><option value="it">Italian</option><option value="ja">Japanese</option><option value="jw">Javanese</option><option value="kn">Kannada</option><option value="kk">Kazakh</option><option value="km">Khmer</option><option value="ko">Korean</option><option value="lo">Lao</option><option value="la">Latin</option><option value="lv">Latvian</option><option value="lt">Lithuanian</option><option value="mk">Macedonian</option><option value="mg">Malagasy</option><option value="ms">Malay</option><option value="ml">Malayalam</option><option value="mt">Maltese</option><option value="mi">Maori</option><option value="mr">Marathi</option><option value="mn">Mongolian</option><option value="my">Myanmar (Burmese)</option><option value="ne">Nepali</option><option value="no">Norwegian</option><option value="fa">Persian</option><option value="pl">Polish</option><option value="pt">Portuguese</option><option value="pa">Punjabi</option><option value="ro">Romanian</option><option value="ru">Russian</option><option value="sr">Serbian</option><option value="st">Sesotho</option><option value="si">Sinhala</option><option value="sk">Slovak</option><option value="sl">Slovenian</option><option value="so">Somali</option><option value="es">Spanish</option><option value="su">Sundanese</option><option value="sw">Swahili</option><option value="sv">Swedish</option><option value="tg">Tajik</option><option value="ta">Tamil</option><option value="te">Telugu</option><option value="th">Thai</option><option value="tr">Turkish</option><option value="uk">Ukrainian</option><option value="ur">Urdu</option><option value="uz">Uzbek</option><option value="vi">Vietnamese</option><option value="cy">Welsh</option><option value="yi">Yiddish</option><option value="yo">Yoruba</option><option value="zu">Zulu</option></select> <select id="SL_lng_to"><option value="af">Afrikaans</option><option value="sq">Albanian</option><option value="ar">Arabic</option><option value="hy">Armenian</option><option value="az">Azerbaijani</option><option value="eu">Basque</option><option value="be">Belarusian</option><option value="bn">Bengali</option><option value="bs">Bosnian</option><option value="bg">Bulgarian</option><option value="ca">Catalan</option><option value="ceb">Cebuano</option><option value="ny">Chichewa</option><option value="zh-CN">Chinese (Simplified)</option><option value="zh-TW">Chinese (Traditional)</option><option value="hr">Croatian</option><option value="cs">Czech</option><option value="da">Danish</option><option value="nl">Dutch</option><option value="en">English</option><option value="eo">Esperanto</option><option value="et">Estonian</option><option value="tl">Filipino</option><option value="fi">Finnish</option><option value="fr">French</option><option value="gl">Galician</option><option value="ka">Georgian</option><option value="de">German</option><option value="el">Greek</option><option value="gu">Gujarati</option><option value="ht">Haitian Creole</option><option value="ha">Hausa</option><option value="iw">Hebrew</option><option value="hi">Hindi</option><option value="hmn">Hmong</option><option value="hu">Hungarian</option><option value="is">Icelandic</option><option value="ig">Igbo</option><option value="id">Indonesian</option><option value="ga">Irish</option><option value="it">Italian</option><option value="ja">Japanese</option><option value="jw">Javanese</option><option value="kn">Kannada</option><option value="kk">Kazakh</option><option value="km">Khmer</option><option value="ko">Korean</option><option value="lo">Lao</option><option value="la">Latin</option><option value="lv">Latvian</option><option value="lt">Lithuanian</option><option value="mk">Macedonian</option><option value="mg">Malagasy</option><option value="ms">Malay</option><option value="ml">Malayalam</option><option value="mt">Maltese</option><option value="mi">Maori</option><option value="mr">Marathi</option><option value="mn">Mongolian</option><option value="my">Myanmar (Burmese)</option><option value="ne">Nepali</option><option value="no">Norwegian</option><option value="fa">Persian</option><option value="pl">Polish</option><option value="pt">Portuguese</option><option value="pa">Punjabi</option><option value="ro">Romanian</option><option value="ru">Russian</option><option value="sr">Serbian</option><option value="st">Sesotho</option><option value="si">Sinhala</option><option value="sk">Slovak</option><option value="sl">Slovenian</option><option value="so">Somali</option><option selected="selected" value="es">Spanish</option><option value="su">Sundanese</option><option value="sw">Swahili</option><option value="sv">Swedish</option><option value="tg">Tajik</option><option value="ta">Tamil</option><option value="te">Telugu</option><option value="th">Thai</option><option value="tr">Turkish</option><option value="uk">Ukrainian</option><option value="ur">Urdu</option><option value="uz">Uzbek</option><option value="vi">Vietnamese</option><option value="cy">Welsh</option><option value="yi">Yiddish</option><option value="yo">Yoruba</option><option value="zu">Zulu</option></select> Text-to-speech function is limited to 200 characters Options : History : Help : Feedback Close